Applicability of Traditional In Vitro Toxicity Tests for Assessing Adverse Effects of Monoclonal Antibodies: A Case Study of Rituximab and Trastuzumab - Kizhedath, Arathi (Antibodies (Basel), 2018)
Monoclonal antibody (mAb) therapeutics have a promising outlook within the pharmaceutical industry having made positive strides in both research and development as well as commercialisation, however this development has been hampered by manufacturing failures and attrition. This study explores the applicability of traditional in vitro toxicity tests for detecting any off-target adverse effect elicited by mAbs on specific organ systems using hepatocarcinoma cell line (HepG2) and human dermal fibroblasts neonatal (HDFn), respectively. The mechanism of antibody dependent cytotoxicity (ADCC), complement dependent cytotoxicity (CDC) via complement activation, and complement dependent cellular cytotoxicity (CDCC) were assessed. Major results: no apparent ADCC, CDCC, or CDC mediated decrease in cell viability was measured for HepG2 cells. For HDFn cells, though ADCC or CDCC mediated decreases in cell viability wasn’t detected, a CDC mediated decrease in cell viability was observed. Several considerations have been elucidated for development of in vitro assays better suited to detect off target toxicity of mAbs.